INNOVATIVE MECHANISMS OF LOGISTICS AND SUPPLY CHAIN MANAGEMENT IN ENHANCING REGIONAL EXPORT COMPETITIVENESS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The article examines the impact of logistics efficiency and supply chain management on export performance using the case of Uzbekistan. The study aims to identify the role of logistics factors in enhancing export activities. The research is based on analytical and comparative methods using data from international organizations. The findings indicate that improvements in logistics infrastructure and management practices contribute to export growth and competitiveness. The results are of practical relevance for export-oriented firms.